OPTIMALISASI PARKING STAND DI TERMINAL 2F BANDARA SOEKARNO-HATTA TAHUN 2015 - Mustika Sari (Institut Transportasi dan Logistik Trisakti, 2016)
One of the airport which is handled by PT Angkasa Pura II and the biggest in Indonesia is Soekarno Hatta Airport,Tanggerang. In 2014, the airport rank is 12nd as the busiest airport in the world (aci report), while the existence of the parking stand is limited. The aim of the research is to analyze the need of parking stand at terminal 2F, especially on the weekend. This research use a queue method with the result; the data is processed with probability 1 or when the airplane in the queue to the parking stand at 46.18%, the utilization value of the parking stand services during weekends 6.02%. Meanwhile, for a regular time the probability is 71.00%, utilization value is 14.70%.